2018
DOI: 10.1007/s10072-018-3479-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of STN-DBS stimulation and different frequency settings on the acoustic-articulatory features of vowels

Abstract: Our results indicated that STN-DBS stimulation at 130 Hz had a significant positive effect on articulation of [a] compared to off-stimulation. Although there is not any statistical significant stimulation at 60 and 230 Hz may also have an effect on the articulation of [e], [i], and [o] but this effect needs to be investigated in future studies with higher numbers of participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…In our study, we used audio features from the Praat software because of their simplicity and wide adoption in speech research. [28][29][30] We also tested MFCC features with our machine learning model. Although MFCC 2 and 12 were significantly associated with pain scores in the univariate mixed model analysis, this did not translate to an improved KNN model accuracy compared with the KNN model trained with Praat features.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used audio features from the Praat software because of their simplicity and wide adoption in speech research. [28][29][30] We also tested MFCC features with our machine learning model. Although MFCC 2 and 12 were significantly associated with pain scores in the univariate mixed model analysis, this did not translate to an improved KNN model accuracy compared with the KNN model trained with Praat features.…”
Section: Discussionmentioning
confidence: 99%
“…Studies consistently indicate that LF stimulation of STN has a positive impact on speech [108,177,178]. One study showed improvements in the articulation of certain vowels at 130 Hz [179] and a significant increase in maximal phonation time (MPT) at 60 Hz compared to 130 Hz and OFF condition following STN-DBS [180]. Moreover, a combination of higher voltage and lower frequency and pulse width has been linked to enhancement of speech outcomes [181].…”
Section: Phonation and Articulationmentioning
confidence: 99%
“…Moreover, a combination of higher voltage and lower frequency and pulse width has been linked to enhancement of speech outcomes [181]. On the other hand, higher frequency stimulation may have variable effects on vocal control and production, with some studies reporting improvements in vocal production [179], while others suggest a negative impact [180,182]. However, no statistically significant differences were found in vocal acoustic measurements between low-frequency (60 Hz) and high-frequency (130 Hz) stimulation [172].…”
Section: Phonation and Articulationmentioning
confidence: 99%
“…Die Stimulationsfrequenz beträgt durchschnittlich 130 Hz. Klinische Beobachtungen und erste Studien zeigten, dass eine hohe Frequenz für die Verbesserung des Tremors von Vorteil sein könnte, wohingegen das Sprechen und der Gang von einer niedrigen Frequenz profitieren (in den Studien definiert als Werte zwischen 60 Hz 71 72 und 110 Hz). Allerdings könnte die allmähliche Rückkehr von Tremor und Akinesie nach etwa 3 Monaten eine Erhöhung der Frequenz auf 130 Hz erforderlich machen 73 .…”
Section: Variabilität Der Sprachreaktion Auf Die Stimulationunclassified